2021
DOI: 10.3390/ani11071945
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Oxidative Stress Biomarkers in the Serum of Healthy Polish Dairy Goats with Those Naturally Infected with Small Ruminant Lentivirus in the Course of Lactation

Abstract: The present study examines the effects of natural infection by small ruminant lentivirus (SRLV) in the two most common goat breeds in Poland, i.e., Polish white improved and polish fawn improved. It focuses on biomarkers of oxidative stress, oxidatively modified proteins and antioxidant defenses, ceruloplasmin level as an acute phase protein, and the activities of antioxidant enzymes in the goat serum. It was conducted on 24 goats divided into two equal groups: one SRLV-seropositive (SRLV-SP) and another SRLV-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 49 publications
(67 reference statements)
0
7
0
Order By: Relevance
“…In addition, Celi et al [ 79 ] stated that the oxidative stress marker responded differently, resulting in a lack of correlation with other parameters during the peripartum period in goats. Copious studies demonstrate changes in oxidative stress markers concerning various physiological states including pregnancy, lactation, and feeding regime in goats [ 3 , 76 , 80 , 81 ], rather than the changes concerning age in the growing period of kids. Various factors are incriminated in the fluctuation of oxidative stress markers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Celi et al [ 79 ] stated that the oxidative stress marker responded differently, resulting in a lack of correlation with other parameters during the peripartum period in goats. Copious studies demonstrate changes in oxidative stress markers concerning various physiological states including pregnancy, lactation, and feeding regime in goats [ 3 , 76 , 80 , 81 ], rather than the changes concerning age in the growing period of kids. Various factors are incriminated in the fluctuation of oxidative stress markers.…”
Section: Discussionmentioning
confidence: 99%
“…Trace minerals, particularly Cu and Zn, constitute a functional component to maintain SOD activity, whereas Se is closely related to GPX [ 82 ]. Unfortunately, most ruminant studies on oxidative stress are related to single insults, especially diseases and nutrition regimes, and physiological alterations in these parameters are still lacking [ 81 ]. Here, we have to say that the fluctuation in the levels of the reported measurements in the current study in association with oxidative stress markers could be ascribed to different stressors associated with changes in the metabolic states due to weaning, the active phase of development of body organs, reproductive changes associated with puberty, and environmental insults necessary for immunologic maturation.…”
Section: Discussionmentioning
confidence: 99%
“…However, another study by Reczyńska et al (2018a) reported an elevated level of APPs (Serum amyloid A) in the serum of subclinical and asymptomatic groups infected with SRLV, while a decrease in the concentration of SAA and Cp (Fig. 4) in the milk of asymptomatic infected goat was evident (Kurhaluk et al 2021).…”
Section: Role Of Acute Phase Proteins In Small Ruminant Lentivirus (S...mentioning
confidence: 90%
“…It also infects epithelial cells too. The virus is single standard RNA virus and is difficult to eliminate because it persists in the latent form in the infected animal for months to years (Jarczak et al 2016;Górecka-Bruzda et al 2019;Kurhaluk et al 2021). It causes arthritis of different joints like mostly carpal and rarely tarsal joint in mature goats.…”
Section: Small Ruminant Lentivirus (Srlv)mentioning
confidence: 99%
See 1 more Smart Citation